Question about SoftMath Algebrator - Algebra Homework Solver (689076614429)

Hi,

a 6ya expert can help you resolve that issue over the phone in a minute or two.

best thing about this new service is that you are never placed on hold and get to talk to real repairmen in the US.

the service is completely free and covers almost anything you can think of (from cars to computers, handyman, and even drones).

click here to download the app (for users in the US for now) and get all the help you need.

goodluck!

Posted on Jan 02, 2017

5x (-3x) = 2x -3x - -3x = 0

The equation then becomes 2x=10 2x/2 = x and 10/2 =5

then x=5. does it work 5x5=10+3*5 YES

The equation then becomes 2x=10 2x/2 = x and 10/2 =5

then x=5. does it work 5x5=10+3*5 YES

Jan 20, 2017 | The Office Equipment & Supplies

5x-y=-5 answer x=-1, y= 5
http://www.wolframalpha.com/input/?i=Determine+the+x+and+y+intercept+of+the+graph+for+equation%3A+5x-y%3D-5

-3x+2y=7 answer x = -7/3, y = 7/2 http://www.wolframalpha.com/input/?i=Determine+the+x+and+y+intercept+of+the+graph+for+equation%3A+-3x%2B2y%3D7

-3x+2y=7 answer x = -7/3, y = 7/2 http://www.wolframalpha.com/input/?i=Determine+the+x+and+y+intercept+of+the+graph+for+equation%3A+-3x%2B2y%3D7

Feb 23, 2015 | Office Equipment & Supplies

get the X's on the same side of the equation by subtracting 3x from both sides, then get the constants on the same side by subtracting 5 from each side. You'll simplify it to 6x-3x=17-5, resulting in 3x=12 or x=4...

Nov 14, 2014 | Computers & Internet

5x -2(x-2) = 6 -2(-3x-3)

5x -2x +4 = 6 +6x +6 (use the distributive property)

3x + 4 = 6x + 12 (collect terms)

4 = 3x + 12 (subtract 3x from both sides to get all x on one side)

-8 = 3x (subtract 12 from both sides to get only x on one side)

-8/3 = x (divide both sides by 3 to get x by itself)

Check

5(-8/3) -2((-8/3)-2) = 6 - 2(-3(-8/3)-3)

-40/3 -2(-8/3-6/3) = 6 - 2(8-3)

-40/3 -2(-14/3) = 6 -2(5)

-40/3 + 28/3 = 6 - 10

-12/3 = -4 (yes)

5x -2x +4 = 6 +6x +6 (use the distributive property)

3x + 4 = 6x + 12 (collect terms)

4 = 3x + 12 (subtract 3x from both sides to get all x on one side)

-8 = 3x (subtract 12 from both sides to get only x on one side)

-8/3 = x (divide both sides by 3 to get x by itself)

Check

5(-8/3) -2((-8/3)-2) = 6 - 2(-3(-8/3)-3)

-40/3 -2(-8/3-6/3) = 6 - 2(8-3)

-40/3 -2(-14/3) = 6 -2(5)

-40/3 + 28/3 = 6 - 10

-12/3 = -4 (yes)

Dec 19, 2010 | Answer Racing Ion Motorcycle Jersey 2010

Here you are :

2X2-3x+5=0 => 4-3x+5=0; (2X2=4) => -3x+9=0; (4+5=9) => 9 = 3x; (-3x moved to the right-hand side and it became 3x) => 9/3=x; (3 moved to the right hand side, so it becomes 1/3, i.e 1/3X9= 9/3) i.e. x=9/3 => x=3

Hence x equals to 3.

You can add or remove the explanation/description, I simply add them to make you understand.

If you need help, let me know.

Good luck.

Thanks for using** FixYa.**

2X2-3x+5=0 => 4-3x+5=0; (2X2=4) => -3x+9=0; (4+5=9) => 9 = 3x; (-3x moved to the right-hand side and it became 3x) => 9/3=x; (3 moved to the right hand side, so it becomes 1/3, i.e 1/3X9= 9/3) i.e. x=9/3 => x=3

Hence x equals to 3.

You can add or remove the explanation/description, I simply add them to make you understand.

If you need help, let me know.

Good luck.

Thanks for using

Oct 08, 2010 | Computers & Internet

Factor out 3X

3X(2X-5)=0

The expression is equal to zero if one of the factors on the left side equals zero.

1st solution: 3X=0, thus X=0

2nd solution 2X-5 = 0 if X=5/2

3X(2X-5)=0

The expression is equal to zero if one of the factors on the left side equals zero.

1st solution: 3X=0, thus X=0

2nd solution 2X-5 = 0 if X=5/2

Sep 10, 2010 | Office Equipment & Supplies

Hi,

**2x - 1/5 - 3x/7 + 2 = x + 9/2 - x - 3/10**

Or, 2x - 3x/7 = 1/5 - 2 + 9/2 - 3/10

Or, (14x + 3)/7 = (2 - 20 + 45 - 3)/10

Or, 11x/7 = 24/10 = 12/5

Or, 11x = 84/5

Or,__x = 84/55__

**
Good luck and have a nice day.
**

Thanks for using Fixya.

Rating the solution is highly appreciated

Or, 2x - 3x/7 = 1/5 - 2 + 9/2 - 3/10

Or, (14x + 3)/7 = (2 - 20 + 45 - 3)/10

Or, 11x/7 = 24/10 = 12/5

Or, 11x = 84/5

Or,

Thanks for using Fixya.

Rating the solution is highly appreciated

Jul 29, 2010 | Computers & Internet

[3(x-5)-4(-3x+2)]-[4(6-x)]

[(3x-15)-(12x+8)]-(24-4x)

(-9x-23)-(24-4x)

-13x-(-1)

this is 9th grade stuff.

[(3x-15)-(12x+8)]-(24-4x)

(-9x-23)-(24-4x)

-13x-(-1)

this is 9th grade stuff.

Sep 13, 2008 | Texas Instruments TI-84 Plus Calculator

I am not quite sure what you are asking...

(1) if asking for graphing y= -2/3x+2, then press [diamond] [F1: Y=] type in .2/3x +2, see graph by [diamond][graph]

(2) if asking for graphing y= -2/3x+a, where a=3x, then first archive a=3x in Home screen by [home], type 3x [sto] a, then go back to y= menu, and type -2/3x+a in Y1

(3) if asking for graphing an equation that is dependent on 2 variables at the same time, use x-y-z axis (aka, change mode to graphing 3-D by [mode]graph [5:3D]) then enter desired equation in y= menu using Z function in terms of x and y aka z(x,y)= ...)

(1) if asking for graphing y= -2/3x+2, then press [diamond] [F1: Y=] type in .2/3x +2, see graph by [diamond][graph]

(2) if asking for graphing y= -2/3x+a, where a=3x, then first archive a=3x in Home screen by [home], type 3x [sto] a, then go back to y= menu, and type -2/3x+a in Y1

(3) if asking for graphing an equation that is dependent on 2 variables at the same time, use x-y-z axis (aka, change mode to graphing 3-D by [mode]graph [5:3D]) then enter desired equation in y= menu using Z function in terms of x and y aka z(x,y)= ...)

May 18, 2008 | Texas Instruments TI-89 Calculator

B. 2((2-Y)/3)-Y=3

2(2-Y)-Y=9

4-2Y-Y=9

-3Y=9-4

-3Y=5

-Y=5/3

Y=-1.67

A. 3X+(-1.67)=2

3X-1.67=2

3X=2+1.67

3X=3.67

X=3.67/3

X=1.22

2(2-Y)-Y=9

4-2Y-Y=9

-3Y=9-4

-3Y=5

-Y=5/3

Y=-1.67

A. 3X+(-1.67)=2

3X-1.67=2

3X=2+1.67

3X=3.67

X=3.67/3

X=1.22

Nov 05, 2007 | SoftMath Algebrator - Algebra Homework...

211 people viewed this question

Usually answered in minutes!

×